2007
DOI: 10.1186/1471-244x-7-47
|View full text |Cite
|
Sign up to set email alerts
|

Presence of depression and anxiety before and after coronary artery bypass graft surgery and their relationship to age

Abstract: Background: Scientific literature on depression and anxiety in patients with coronary heart disease (CHD) consistently reports data of elevated anxiety and depression scores indicating clinically relevant quantities of these psychopathological conditions. Depression is considered to be a risk factor for the development of CHD and deteriorates the outcome after cardiac rehabilitation efforts. The aim of our study was to evaluate the presence of clinically relevant anxiety and depression in patients before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
3
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 24 publications
6
56
3
11
Order By: Relevance
“…Depression being one of the least reported symptoms is consistent with the results of Barnasonet al, (2000), Krannich et al, (2007) and Zimmerman et al (2004). In contrast, Rymaszewska (2003) found the depression score ranged from mild to moderate after cardiac surgery.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Depression being one of the least reported symptoms is consistent with the results of Barnasonet al, (2000), Krannich et al, (2007) and Zimmerman et al (2004). In contrast, Rymaszewska (2003) found the depression score ranged from mild to moderate after cardiac surgery.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies found that both the psychological symptoms of anxiety and depression were frequently reported (Doering, et al, 2002;Koivla et al, 2010;Lee, 2009;Malik et al, 2005;Utriyaprasit et al, 2010) while others showed lower frequencies in both such as Gallgher and McKinley (2009) ;Krannich, et al, (2007). In this study anxiety was found to be high whereas depression was found to be low.…”
Section: Discussionmentioning
confidence: 48%
“…The sample of the aforementioned study presented an average of age close to 60 years, i.e., higher than the one of our study. Studies demonstrate that older patients have more mood disorders in the preoperative period, despite not evaluating the relation of these disorders with spiritual well-being, disregarding the religiosity and the subjectivity in the experience of surgical procedure (11) . A survey conducted in a national reference center, when comparing the manners of hosting in the preoperative period, Note: Avg ± sd -average ± standard deviation; SWBT -total spiritual well-being; RWB -religious well-being; EWB -existential well-being.…”
Section: Discussionmentioning
confidence: 99%
“…CABG lahko sproži številne neugodne čustvene in telesne simptome. Anksioznost se pojavlja pri 20-55 % bolnikov (Slika 2), ki potrebujejo CABG (31). Je napovedni dejavnik za slabšo napoved izida (32).…”
Section: Spl-pop -Splošna Populacija Kb -Koronarna Bolezen Srca Pciunclassified
“…Mlajši bolniki so bili pred CABG bolj anksiozni, po operaciji pa je anksioznost močno upadla, medtem ko je ostala pri starejših anksioznost bolj ali manj enaka. Avtorji to razlagajo s hipotezo, da je anksioznost pri mlajših povezana s strahom pred smrtjo med operacijo in ne toliko z manjšo telesno simptomatiko koronarne bolezni, česar si želijo predvsem starejši (31). Bolniki pod 65 leti imajo večje tveganje za pooperativni strah in anksioznost, zato sta pomembna prepoznava anksioznosti in nudenje ustrezne pomoči pred operacijo (36).…”
Section: Spl-pop -Splošna Populacija Kb -Koronarna Bolezen Srca Pciunclassified